PELAYANAN PENERBITAN SURAT IZIN TEMPAT USAHA( SITU ) PADA KANTOR PELAYANAN TERPADU KABUPATEN HULU SUNGAI UTARA - Agus Surya Dharma (AS-SIYASAH: Jurnal Ilmu Sosial Dan Ilmu Politik, 2017)
The Public Service is juring service by government, enterpreneur on government’s nama or entrepreneur to society with or without payment for filling necessary or society needs.Based on prior research was found that there was lateness problem in completion to make SITU that exceed time from determined time in procedure operational standard of service integrated office Hulu Sungai Utara District. The Purpose of this research are to describe and analyze : (1) How process permission servise in publication of work place permission letter (SITU) in Hului Sungai Utara District. (2) Factors that influence service publishing of work plece permission letter.The approach of research is qualitative. The plece of research is in service integrated office in HSU District. The technique of collecting data is done by depth interview, observation and documentation. The analysis data uses interaction model by Miles and Huberman. The data testing is done with triangulation, that is technique triangulation although source triangulation. The result of research showed that servies of KPT HSU District in SITU service is high enough. This fact is appeared from (1) kid of apparatus sources and related with their skills. (2) The ease in submission is done well. It is announced dearly about making of permission letter procedure. (3) The accuracy of service that free from mestaker is well done. It canbe seen from there is no mestaker in every publication of fermission document. (4) The service cost in well enough. It is appeared from transparency about amount of payment with out more tax. (5) Many employees heve SLTA education so that their qualities in education aspect is felt still low enough.